Parameterizing Tabular‐Iceberg Decay in an Ocean Model - A. Huth; A. Adcroft; O. Sergienko (Journal of Advances in Modeling Earth Systems, 2022)
Abstract Large tabular icebergs account for the majority of ice mass calved from Antarctic ice shelves, but are omitted from climate models. Specifically, these models do not account for iceberg breakup and as a result, modeled large icebergs could drift to low latitudes. Here, we develop a physically based parameterization of iceberg breakup based on the “footloose mechanism” suitable for climate models. This mechanism describes breakup of ice pieces from the iceberg edges triggered by buoyancy forces associated with a submerged ice foot fringing the iceberg. This foot develops as a result of ocean‐induced melt and erosion of the iceberg freeboard explicitly parameterized in the model. We then use an elastic beam model to determine when the foot is large enough to trigger calving, as well as the size of each child iceberg, which is controlled with the ice stiffness parameter. We test the breakup parameterization with a realistic large iceberg calving‐size distribution in the Geophysical Fluid Dynamics Laboratory OM4 ocean/sea‐ice model and obtain simulated iceberg trajectories and areas that closely match observations. Thus, the footloose mechanism appears to play a major role in iceberg decay that was previously unaccounted for in iceberg models. We also find that varying the size of the broken ice bits can influence the iceberg meltwater distribution more than physically realistic variations to the footloose decay rate.